2011
DOI: 10.1242/jcs.089516
|View full text |Cite
|
Sign up to set email alerts
|

Unique amino acid signatures that are evolutionarily conserved distinguish simple-type, epidermal and hair keratins

Abstract: SummaryKeratins (Ks) consist of central a-helical rod domains that are flanked by non-a-helical head and tail domains. The cellular abundance of keratins, coupled with their selective cell expression patterns, suggests that they diversified to fulfill tissue-specific functions although the primary structure differences between them have not been comprehensively compared. We analyzed keratin sequences from many species: K1, K2, K5, K9, K10, K14 were studied as representatives of epidermal keratins, and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 65 publications
1
58
0
Order By: Relevance
“…6D). MAP3K1 ablation decreased the expression of keratin 17, a hair follicle and epidermal appendage marker; it also down-regulated the expression of keratins 25 and 27, which are type I intermediate filaments, and keratins 71 and 73, which are type II intermediate filaments, and trichohyalin ( Tchh ) and hair keratin-associated proteins (KRTAP), which are intermediate filament-associated proteins specifically implicated in inner root sheath of hair follicles(Gritli-Linde et al, 2007;Strnad et al, 2011). These observations led us to ask whether MAP3K1 ablation affected the development and structure of hair follicle and epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…6D). MAP3K1 ablation decreased the expression of keratin 17, a hair follicle and epidermal appendage marker; it also down-regulated the expression of keratins 25 and 27, which are type I intermediate filaments, and keratins 71 and 73, which are type II intermediate filaments, and trichohyalin ( Tchh ) and hair keratin-associated proteins (KRTAP), which are intermediate filament-associated proteins specifically implicated in inner root sheath of hair follicles(Gritli-Linde et al, 2007;Strnad et al, 2011). These observations led us to ask whether MAP3K1 ablation affected the development and structure of hair follicle and epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…The DEC205 binding data show that it only recognizes the C-terminal tail domains of keratin 1 and keratin 10, and notably, the binding tests can be done by Western blot assays, suggesting that the target sequence of DEC205 on keratins adopts a linear conformation. Indeed, the tail domains of keratin 1 and keratin 10 contain a high percentage of glycine and serine in a X(Y) n format, where X represents an aromatic or a long-chain aliphatic residue and Y is either glycine or serine (32,37). The X(Y) n pattern is quasirepetitive and may form "glycine loops" where the Gly-rich peptides have flexible loop-like structures without rigid conformations (37), thus explaining the results of Western blot assays.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a bacterial protein ClfB could recognize the Gly-rich tail domain of keratin 8 and keratin 10 (38, 39), and the crystal structure of ClfB complexed with the keratin 10 tail shows that the Gly-rich sequence also adopts a linear conformation (29). In fact, the Gly-rich sequences are found in the C-terminal tail domains of many keratin members including both type I and type II keratins (32,37), suggesting that DEC205 might be a generic receptor for keratins targeting to these sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The designation “intermediate filaments” conveys that their diameter, ~10 nm, is intermediate between those of actin microfilaments (~6–8 nm) and microtubules (~25 nm) (Ishikawa et al 1968). Proteins belonging to this large superfamily, comprisingapproximately 70 conserved genes, show substantial amino acid sequence diversity, with some sharing as little as 20% identity (Szeverenyi et al 2008; Strnad et al 2011). Regardless of this heterogeneity, each memberof the IF familyshares a tripartite protein substructure, with a family-defining, centrally located α-helical rod domain, and readily self-assembles to form 10-nm filaments on its own or, more commonly, in partnership with other IF proteins (Fig.…”
Section: Introductionmentioning
confidence: 99%